Characterisation of Metagenomic Bougainvillea Soil DNA Through rDNA PCR Amplification - Ganesan, Aruna (2017)
Rhizosphere is an important part of soil ecosystem, being a habitat for a vast amount of bacteria that is influenced by root secretions, which contribute to the richness of bacteria in the soil. Conventional culturing often is not able to simulate the environmental settings microorganisms are adapted to, thus posing barrier for the advancement in environmental and clinical microbiology. Metagenomics evades this unculturability by analysing genomic variability of bacteria in environmental samples and this process starts off with DNA extraction. The aim of this research is to select several soil samples, extract the DNA from the microbiota within, and analysed. Soil samples were collected under bougainvillea shrubs for DNA isolation. All the samples were analysed using agarose gel electrophoresis, restriction digestion, polymerase chain reaction and spectrophotometer. CTAB DNA extraction produced intact high molecular weight band on agarose gel suggesting intact metagenomics DNA was isolated and had moderate A260/A280 ratio indicating moderate purity from protein contamination. From the sequencing data, identification of plant growth promoting microorganisms can be done which are beneficial to the field of agriculture.